2021
DOI: 10.1101/2021.10.28.463794
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemogenetic Stimulation of Tonic Locus Coeruleus Activity Strengthens the Default Mode Network

Abstract: The default mode network (DMN) of the brain is involved in cognition, emotion regulation, impulsivity, and balancing between internally and externally focused states. DMN dysregulation has been implicated in several neurological and neuropsychiatric disorders. In this study, we used functional magnetic resonance imaging (fMRI), positron emission tomography (PET), and spectral fiber-photometry to investigate the selective neuromodulatory effect of norepinephrine (NE)-releasing noradrenergic neurons in the locus… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 111 publications
(209 reference statements)
2
29
0
Order By: Relevance
“…We used an fMRI-compatible, spectrally resolved, fiber-photometry platform (Bao et al, 2020; Chao et al, 2022; Das et al, 2021; Meng et al, 2018; Oyarzabal et al, 2022; Zhang et al, 2022b, 2022a) with four recording fibers ( Figure 1A ) to measure neuronal GCAMP activity in the RSC, Cg, PrL, and AI from rats ( Supplementary Figure 1 ). GCaMP activity was combined with whole-brain fMRI recordings in anesthetized rodents to capture concurrent resting-state signals from both modalities ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We used an fMRI-compatible, spectrally resolved, fiber-photometry platform (Bao et al, 2020; Chao et al, 2022; Das et al, 2021; Meng et al, 2018; Oyarzabal et al, 2022; Zhang et al, 2022b, 2022a) with four recording fibers ( Figure 1A ) to measure neuronal GCAMP activity in the RSC, Cg, PrL, and AI from rats ( Supplementary Figure 1 ). GCaMP activity was combined with whole-brain fMRI recordings in anesthetized rodents to capture concurrent resting-state signals from both modalities ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…The first goal of our study was to investigate intrinsic neuronal coupling between putative rodent DMN nodes in the resting state condition. While studies using resting-state fMRI have suggested that the rat DMN is comprised of the RSC, Cg, and PrL (Gozzi and Schwarz, 2016;Hsu et al, 2016;Ji et al, 2018;Lee et al, 2021;Liang et al, 2018;Lu et al, 2012;Osmanski et al, 2014;Oyarzabal et al, 2022;Paasonen et al, 2018;Peeters et al, 2020a;Tu et al, 2021bTu et al, , 2021aXu et al, 2022), such coupling…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neuromodulation is suggested to elicit rapid rhythmic network reconfiguration among larger circuits as well. For example, norepinephrine appears to contribute to rapid changes in synchronization of multiple vertebrate brain regions during switches in attention (Bouret and Sara 2005; Oyarzabal et al 2022; Ramirez et al 2016). Disordered inter-network coordination and decreased flexibility in oscillatory networks can lead to dysphagia, memory and locomotor deficits, and disruption of cognitive processes (Barlow 2009; Moore et al 2014; Rangel et al 2016).…”
Section: Discussionmentioning
confidence: 99%